Analysis of the Role of Waiters in Improving Service Quality at Seafood Restaurant NDC Resort & Spa Manado - Devini Nadia Budiman; Fonny Sangari; Yurike Sintia Lewan (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the role of waiters in supporting service quality at Seafood Restaurant, NDC Resort & Spa Manado, using the SERVQUAL framework.Research Methodology: A descriptive qualitative approach was employed over approximately two weeks in May 2026. Participants were selected through purposive sampling, involving four waiters and four restaurant guests. Data were collected through observation, semi-structured interviews, and documentation. The data were organized, coded, and interpreted based on the five SERVQUAL dimensions as a qualitative analytical framework.Results: The findings indicated that waiter roles were reflected across all SERVQUAL dimensions. Restaurant cleanliness became less consistent during busy periods, while order accuracy was generally maintained despite occasional errors. Response time decreased during peak hours due to higher guest volumes. Some waiters required additional confirmation when providing menu information. Nevertheless, friendly communication, personal attention, and courteous service were consistently demonstrated.Conclusions: The study provides a qualitative understanding of waiter roles in daily restaurant operations and shows that service quality consistency is influenced by operational factors, including peak hours, workload distribution, guest volume, and staff coordination.Limitations: The research was conducted at a single restaurant over a two-week period. Therefore, the findings describe only the selected operational setting and should not be generalized to other hospitality businesses.Contributions: The study demonstrates how the SERVQUAL framework can be applied to interpret waiter roles in a hotel restaurant and may provide practical insights for restaurant management when reviewing service practices.